Fresh Chicken Farm / Mohamad Shukry Maksah ... [et.al] - Mohamad Shukry, Maksah; Fairuz, Johari; Muhd Nurfaiz, Baharuddin; Ahmad Luqman, Mohamed Shaihani (Faculty of Electrical Engineering, 2005)
This business is based on partnership where it consists of four (4) members. The members consist of the General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM372,410 where the total contribution of each member is RM79,910 and the rest is from the Bank Pertanian loan. FRESH CHICKEN FARM is a company related to the breeding the chicken meat. Our market focus is for the Pertanian Pertiwi, a company that directly deals with us, they will supply the day-old-chicks with the certain price and buy the chicken back when it reach at certain age (normally at 50 days). For those who are interested to buy the fresh chickens, we can't sell to them due to our contract with the Pertanian Pertiwi.